Impact of Chemical and Biological Fungicides Applied to Grapevine on Grape Biofilm, Must, and Wine Microbial Diversity - Escribano-Viana, Rocío; López-Alfaro, Isabel; López, Rosa; Santamaría, Pilar; Gutiérrez, Ana R.; González-Arenzana, Lucía (Frontiers in Microbiology, 2018)
This study was aimed to measure the impact of the application of a bio-fungicide against Botrytis cinerea on the microbiota involved in the alcoholic fermentation of Tempranillo Rioja wines. For this purpose, a bio-fungicide composed of the biological control bacterium Bacillus subtilis QST713 was applied to the vineyard. The microbial diversity was analyzed from grape biofilm to wine. Impact on microbial diversity was measured employing indexes assessed with the software PAST 3.10 P.D. Results were compared to non-treated samples and to samples treated with a chemical fungicide mainly composed by fenhexamid. Overall, the impact of the bio-fungicide on the microbial diversity assessed for grape biofilm and for musts was not remarkable. Neither of the tested fungicides enhanced the growth of any species or acted against the development of any microbial groups. The bio-fungicide had no significant impact on the wine microbiota whereas the chemical fungicide caused a reduction of microbial community richness and diversity. Although environmental threats might generate a detriment of the microbial species richness, in this study the tested bio-fungicide did not modify the structure of the microbial community. Indeed, some of the Bacillus applied at the grape surface, were detected at the end of the alcoholic fermentation showing its resilience to the harsh environment of the winemaking; in contrast, its impact on wine quality during ageing is yet unknown.